2013
DOI: 10.1038/clpt.2013.148
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutics for the Treatment of Familial Mediterranean Fever: From Colchicine to Biologics

Abstract: Familial Mediterranean fever (FMF), an inherited autosomal recessive disorder, is characterized by sporadic, paroxysmal attacks of fever and serosal inflammation, lasting 1-3 days. Patients may develop renal amyloidosis, arthritis, serositis, and skin and oral lesions. Diagnosis is based on clinical features, response to treatment with colchicine, and genetic analysis. Colchicine prevents attacks and renal amyloidosis, in addition to reversing proteinuria. Nonresponders may receive novel therapy, including int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 69 publications
0
46
0
7
Order By: Relevance
“…However, it has been demonstrated that polymorphonuclear neutrophils are also a source of ChT (26). Colchicine inhibits the chemotaxis of neutrophils and the release of arachidonate and 5-lipoxygenase in macrophages (27). In our study, 76 patients were receiving colchicine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that polymorphonuclear neutrophils are also a source of ChT (26). Colchicine inhibits the chemotaxis of neutrophils and the release of arachidonate and 5-lipoxygenase in macrophages (27). In our study, 76 patients were receiving colchicine.…”
Section: Discussionmentioning
confidence: 99%
“…In the later group, daily dose is decreased to alternate day or thrice a week after clinical remission is reached or rarely increased two-to threefold the recommended dose in case of relapse or partial response. The dose is also modifi ed in patients on hemodialysis [ 46 ]. Among the three anti-IL-1 agents, anakinra is the most extensively used one.…”
Section: Anakinramentioning
confidence: 99%
“…55 Anakinra is a response modifier that acts by antagonizing the biological effects of IL1, which is a proinflammatory cytokine. The drug is currently approved by the FDA for the treatment of rheumatoid arthritis.…”
Section: Anakinra and Biological Agentsmentioning
confidence: 99%